Does population density moderate suicide risk? An Italian population study over the last 30 years - Monica Vichi; Benedetto Vitiello; Silvia Ghirini; Maurizio Pompili (European Psychiatry, 2020)
AbstractBackground.The relationship between population density and suicide risk remains unclear. While urbanization is associated with greater risk for psychopathology, higher suicide rates have been reported in rural areas. We examined population density and suicide in the Italian population in the last 30 years.Methods.The Italian National Institute of Statistics databases of the Italian population aged 15 years and older (52.4 million in 2016) were used to compute age-adjusted annual total mortality and suicide rates for the years 1985–2016. According to the European Union statistical office (EUROSTAT) criteria, municipalities were classified into densely populated areas, intermediate density areas, or thinly populated areas. Rate ratios (RRs) were computed by sex, age, and geographical area, using densely populated areas as reference.Results.Total mortality was not associated with population density. In males, suicide rate increased with decreasing population density (RR = 1.17, 95% confidence interval [CI]:1.08–1.28, in intermediate population areas, and RR = 1.32, 95% CI: 1.20–1.45, in thinly populated areas, in 2016). This inverse relationship was found across age, geographical areas, and consecutively over 22 years (1994–2016). In females, no significant difference was detected (RR = 0.96, 95% CI: 0.82–1.13 in intermediate density areas and RR = 1.02, 95% CI: 0.85–1.22 in thinly populated areas). Hanging was the most common suicide method among males, more frequent in thinly (58.8%) than intermediate (53.2%) or densely (41.4%) populated areas.Conclusions.A consistent and temporally stable inverse relationship between population density and suicide was found in the male, but not female, population. Men may be more vulnerable to adverse social and economic factors associated with lower population density.